Cheap Talk and the Fed: A Theory of Imprecise Policy Announcments - Stein, Jeremy C. (American Economic Review, 1989)
This paper examines the problem faced by the Federal Reserve in announcing its private information about its future policies. Because it would like to manipulate expectations and pursue a time-inconsistent policy, the Fed cannot reveal its policy objectives precisely and credibly. It can, however, communicate some information about its goals through the cheap talk mechanism of Vincent Crawford and Joel Sobel: making announcements that are imprecise, and only giving ranges within which these goals may lie. Copyright 1989 by American Economic Association.